1999
DOI: 10.1016/s0022-5347(05)68269-9
|View full text |Cite
|
Sign up to set email alerts
|

The Causes of Patient Dropout From Penile Self-Injection Therapy for Impotence

Abstract: To our knowledge this study is the largest published, single center cohort of patients treated with injection and followed for an analysis of dropout rates. Based on study data a reduction in dropout rates may be achieved by keeping the cost of therapy low, and ensuring patient and partner education as well as continued support throughout treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 16 publications
0
28
0
1
Order By: Relevance
“…We conservatively assumed that theutility gain of sildenafil and papaverine-phentolamine injections would be the same. Given the low acceptability of injection therapy, 9 10 this assumption probably overestimates the benefits of injection therapy.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…We conservatively assumed that theutility gain of sildenafil and papaverine-phentolamine injections would be the same. Given the low acceptability of injection therapy, 9 10 this assumption probably overestimates the benefits of injection therapy.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Recent data on ED treatment outcome have shown that many patients discontinue treatment, despite the availability of efficacious pharmacotherapies. Drop-out rates as high as 50% have been described in several studies [89][90][91]. Many issues, other than efficacy or safety, have implications in drop-outs.…”
Section: Future Directionsmentioning
confidence: 99%
“…De plus, les patients autant que leur partenaire préfèrent nettement les formes de thérapeutique les moins invasives [14] et de nombreuses partenaires féminines craignent que les injections intracaverneuses, par exemple, puissent blesser le patient et entraîner des complications [15]. C'est une des raisons pour lesquelles on rencontre un nombre relativement élevé de patients arrêtant leur traitement.…”
Section: La Qualité De Vie Des Partenaires Fémininesunclassified